Pengaruh Metode Diskusi dan Pemberian Tugas terhadap Pencapaian Hasil Belajar Siswa SMK YPM di Kota Sidoarjo Melalui Motivasi Belajar sebagai Variabel Intervening - Chamariyah Chamariyah; Fifit Sujianti; Wasis Budiarto (Universitas 45 Surabaya, 2024)
Fifit Sujianti, 2024. The Influence of Discussion Methods and Giving Assignments on the Achievement of Learning Outcomes of YPM Vocational School Students in Sidoarjo City Through Learning Motivation as an Intervening Variable. Wijaya Putra University Postgraduate Program Surabaya.This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 120 people. The sampling method uses purposive sampling, the analysis tool uses Smart PLS (Partial Least Square). The aim of this research is to describe the relationship between discussion methods, assignments, learning motivation and achievement of learning outcomes for YPM Vocational School students in Sidoarjo City. The research results show that: 1) the discussion method has a significant effect on student learning outcomes with a p value of 0.001 and an original sample value of 0.590; 2) The discussion method has a significant effect on student learning motivation with a p value of 0.000 and an original sample value of 0.297; 3) Giving assignments has a significant effect on learning motivation with a p value of 0.000 and an original sample value of 0.305. 4) Giving assignments has an insignificant effect on achieving learning outcomes with a p value of 0.818 and an original sample value of 0.014; 5) Learning motivation has a significant effect on student achievement of learning outcomes with a p value of 0.000 and an original sample value of 0.649 (dominant influence); 6) The discussion method has a significant effect on the achievement of learning outcomes with learning motivation as an intervening variable with a p value of 0.000 and an original sample value of 0.383; 7) Giving assignments has a significant effect on achieving learning outcomes with learning motivation as an intervening variable with a p value of 0.000 and an original sample value of 0.193.